Penyusunan Succession Planning & Career Planning pada Perusahaan Konstruksi PT. ANgkasa Engineer Indonesia - Alden Nelson,; Mualifah Nurhidayati,; Sheril Fitri Riana,; Lusiana,; Fenny,; Moderin, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study was to determine the preparation of Succession Planning and Career Planning at the Construction Company PT. Angkasa Engineers Indonesia is looking for a new Purchasing Manager position. Succession planning is creating a new paradigm for information, fostering loyalty among employees, and increasing employee morale as part of an employee engagement strategy. The existence of succession planning and career planning for construction companies is very important, namely to prepare new talent, and can help an individual to find out strengths, weaknesses, skills and abilities. The results showed that the succession planning at PT. Angkasa Engineers Indonesia to occupy the position of Purchasing Manager must have criteria and conditions such as: Minimum education S1 Accounting / Economics, has worked in the company for more than 5 years, experienced in the field, in accordance with the terms and conditions that apply.